1998
DOI: 10.1007/bf03164785
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative sacroiliac joint scintigraphy in normal subjects and patients with sacroiliitis

Abstract: The aim of this study is to determine the sacroiliac index (SII) of healthy subjects and to compare these values with patients having sacroiliitis (SI). Quantitative sacroiliac scintigraphy (QSS) was performed with Tc-99m hydroxy methylene diphosphonate (HMDP) and whole sacroiliac joint-to-sacrum ratio was calculated as a SII by the region of interest (ROI) method. Forty-seven nonarthritic healthy subjects and 13 patients with SI were studied. Effects of aging, gender and laterality on SII were evaluated in 47… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Combination of Tc-99m methylene diphosphonate (MDP) bone scintigraphy and Tc-99m nanocolloid bone marrow scintigraphy has showed that Tc-99m nanocolloid scintigraphy can diagnose acute inflammatory sacroiliitis ( 1 ). It has been demonstrated that the addition of quantitative methods (comparing the sacroiliac joint activity with background activity like sacrum) to bone scintigraphy has revealed increase in the sensitivity and has pointed the results in agreement with clinical findings ( 2 ).…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Combination of Tc-99m methylene diphosphonate (MDP) bone scintigraphy and Tc-99m nanocolloid bone marrow scintigraphy has showed that Tc-99m nanocolloid scintigraphy can diagnose acute inflammatory sacroiliitis ( 1 ). It has been demonstrated that the addition of quantitative methods (comparing the sacroiliac joint activity with background activity like sacrum) to bone scintigraphy has revealed increase in the sensitivity and has pointed the results in agreement with clinical findings ( 2 ).…”
Section: Introductionmentioning
confidence: 80%
“…Quantitative methods have been utilized in order to increase diagnostic power of scintigraphy ( 2 , 24 , 25 ). Recently SPECT/CT analysis has been performed by Cusi et al in order to investigate patients with peri-partum pain for >2 years and revealed 95% sensitivity and 99% specificity ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are difficulties in attributing scintigraphic abnormalities to SI joint disease in some horses because of a degree of overlap in quantitative ROI data between these and both normal horses and those lame due to an unrelated cause. There is also controversy about the usefulness of nuclear scintigraphy for the identification of pathological abnormalities of the SI joint in man (Miron et al 1983;Vesterskold et al 1994;Slipman et al 1996;Kacar et al 1998;Braun et al 2000). Various age-and sexrelated changes have been described, but there is lack of consensus.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in the nuclear medicine field had some drawbacks in quantifying the SIS ratio due to overlapping of the adjacent structures without a definite demarcation of the bony structure [ 8 ]. Some papers have insisted the usefulness of early detection of AS by bone scintigraphy [ 31 , 32 ] or SPECT alone [ 33 ]; however, their conclusions are not commonly accepted, and shows limited value for diagnosing probable or suspected AS as well as established AS [ 8 ]. SPECT offers more information than planar imaging of the SI joint; however, accurate delineation of the SI joint or sacrum is nearly impossible.…”
Section: Discussionmentioning
confidence: 99%